Book Circulation Between Spain and the Viceroyalty of Peru in the Late Eighteenth Century [la Circulación del Libro Entre España y el Virreinato del Perú a Fines del Siglo Xviii] - Hachim-Lara, L (CSIC Consejo Superior de Investigaciones Cientificas, 2019)
This article studies book circulation between Spain and the Peruvian Viceroyalty at the end of the eighteenth century. Based on a systematic review, carried out in the Real Aduana collection from the Archivo General de la Nación del Perú, it analyses 48 shipments with books imported from Cádiz to Callao between 1779 and 1789, to be sold in Lima and, to a lesser extent, in other cities such as Santiago de Chile, Cuzco and Guayaquil. The text is divided into two sections. The first reviews the framework of the cultural history of the book and preexisting bibliography, to conclude subsequently that, despite its valuable contributions, this has focused on the sixteenth and seventeenth centuries and has not examined the “entry records” of Callao, but only on the “exit records” kept in the Archivo General de Indias. The second section presents a first evaluation of the data gathered from primary sources, comparing these to the information already known about the transit of books to Peru. This allows us to conclude, among other ideas of interest, that the period studied was characterized by: the secularization of bibliographic material, mainly due to an increase in scientific books; the coexistence of traditional and modern works; Spanish printers’ total understanding of the viceregal market, which received its editions the same year they appeared or shortly thereafter; and the effective reception of imported books by Viceroyalty inhabitants. © 2019 CSIC.